CARBON PASTE ELECTRODE MODIFIED BY CARBON NANOTUBES AND MOLECULARLY IMPRINTED POLY (3-AMINOPHENOL) FOR VOLTAMMETRIC DETERMINATION OF PARACETAMOL - ABRAHAM MORA (NIM: 10512014),
In this research, carbon paste electrode modified with carbon nanotube and molecularly immprinted poly (3-aminophenol) (CPE-CNT-MIP) for voltammetric determination of paracetamol had been succesfuly developed. The modified electrode was made by dispersing CNT (2 mg/mL) on the surface of CPE followed by electropolymerization of 3-aminophenol using 15 cycle of potential in the potential range of -0.2 V - 1.2 V with scan rate of 100 mV/s in HClO4 0.1 M solution containing 3-aminophenol and paracetamol. To produce MIP, paracetamol was removed from polymer matrix with 10 cycle of potential in the same potential range in HClO4 0.1 M solution. Paracetamol measurements were conducted with square wave voltammetry technique. Repeated measurement of paracetamol 0.1 mM resulted in RSD of 5.70% (n = 20). The best calibration curve was found in the concentration range of 6 x 10-4 mM - 1 x 10-1 mM (r2 = 0.9965) and a detection limit of 0,480 μM. Determination of paracetamol in 3 samples of commercial drugs resulted in percent recovery between 99.77% and 104.88%; The results was in accordance with those of spectrophotometric.